A statistical study of solar radio Type III bursts and space weather implication. Issue 4 (15th February 2021) - Ndacyayisenga, Theogene; Uwamahoro, Jean; Sasikumar Raja, K.; Monstein, Christian
Abstract: Solar radio bursts (SRBs) are the signatures of various phenomenon that happen in the solar corona and interplanetary medium (IPM). In this article, we have studied occurrence of Type III bursts and their association with the Sunspot number. This study confirms that occurrence of Type III bursts correlate well with Sunspot number. Further, using the data obtained using e-CALLISTO network, we have investigated drift rates of isolated Type III bursts and duration of the group of Type III bursts. Since Type II, Type III and Type IV bursts are signatures of solar flares and/or CMEs, we can use the radio observations to predict space weather hazards. In this article, we have discussed two events that have caused near Earth radio blackouts. Since e-CALLISTO comprises more than 152 stations at different longitudes, we can use it to monitor the radio emissions from the solar corona 24 h a day. Such observations play a crucial role in monitoring and predicting space weather hazards within few minutes to hours of time.